Preparation of Anti-Aristolochic Acid I Monoclonal Antibody and Development of Chemiluminescent Immunoassay and Carbon Dot-Based Fluoroimmunoassay for Sensitive Detection of Aristolochic Acid I - Ai-Fen Ou (MDPI AG, 2021)
Aristolochic acid (AA) toxicity has been shown in humans regarding carcinogenesis, nephrotoxicity, and mutagenicity. Monitoring the AA content in drug homologous and healthy foods is necessary for the health of humans. In this study, a monoclonal antibody (mAb) with high sensitivity for aristolochic acid I (AA-I) was prepared. Based on the obtained mAb, a chemiluminescent immunoassay (CLEIA) against AA-I was developed, which showed the 50% decrease in the RLUmax (IC50) value of 1.8 ng/mL and the limit of detection (LOD) of 0.4 ng/mL. Carbon dots with red emission at 620 nm, namely rCDs, were synthesized and employed in conventional indirect competitive enzyme-linked immunosorbent assay (icELISA) to improve the assay sensitivity of a fluoroimmunoassay (FIA). Oxidized 3,3′′,5,5′′-tetramethylbenzidine dihydrochloride (oxTMB) can quench the emission of the rCDs through the inner-filter effect; therefore, the fluorescence intensity of rCDs can be regulated by the concentration of mAb. As a result, the assay sensitivity of FIA was improved by five-fold compared to CLEIA. A good relationship between the results of the proposed assays and the standard ultra-high performance liquid chromatography-triple quadrupole mass spectrometer (UPLC-QQQ-MS/MS) of real samples indicated good accuracy and practicability of CLEIA and FIA.